Quantitative relationship between unsuitable water intake time at Qingcaosha reservoir and river discharge under different northerly wind speeds - Guo, Xinyi; Ma, Rui; Zhu, Jianrong (Frontiers in Marine Science, 2025)
Estuarine saltwater intrusion is mainly controlled by river discharge, tide and wind. It is important for utilization of estuarine freshwater to study quantitative relationship between unsuitable water intake time and river discharge. A two-way nested unstructured quadrilateral grid, finite-differencing, three-dimensional estuarine and coastal ocean model (UFDECOM-i) was applied to simulate the saltwater intrusion in the Changjiang Estuary and to get the quantitative relationship between unsuitable water intake time at Qingcaosha Reservoir and river discharge under different northerly wind speeds. The results of numerical experiments show that the salinity at the water intake of Qingcaosha Reservoir is very sensitive to the variation in river discharge. Under 7 day northerly wind of 10 m/s, when the river discharge is 8000 m3/s, the entire estuary is occupied by saline water; the net unit width salt flux (NUSF) landward flows in the North Channel, then flows into the South Channel toward sea, forming a horizontal salt transport route of “flowing into the North Channel and out in the South Channel” due to the strong landward Ekman transport. When the river discharge is 12000 m3/s, the horizontal salt transport route is weakened with the increase of river discharge. Under 7 day northerly wind of 15 m/s, saltwater intrusion increases significantly with the increase of wind speed, and the pattern of NUSF become much stronger. The salinity increases enormously after the action of persistent strong northerly wind. The quantitative relationship between river discharge and the longest continuous unsuitable water intake time of Qingcaosha Reservoir is expressed by formula under climatic wind, 7 day northerly wind of 10 m/s and 15 m/s, respectively, with correlation coefficient R2 of greater than 0.97, which can provide a basis for reservoir water intake and water supply safety.